Impacts Of Interracial Weddings On The Cultural Traditions From Malay Perspective - Ahmad Abu-Dayyeh, Shaima’ Walid (2022)
Malaysia is one of South East Asia’s great countries that is thriving fast with tourism, hospitality, and event management being of its major key industries, especially the cultural tourism sector. Recently, Malaysia has turned out as one of the great destinations for tourism, and this turned out to have an enormous impact on interracial weddings acceptance and its growth in Malaysia. This study debates the impacts on the cultural traditions and cultural tourism that may occur from an interracial wedding between the Malays and the Indian Muslims from the perspective of the Malays. This study displays the rituals and practices of both cultures and marks what can cause impact/s cultural tourism and traditions for an interracial wedding. The research contains information about both cultures, the differences, and the similarities of diverse rituals and practices between the couples. Moreover, interracial wedding conflicts place various emotions, struggles surrounded by values and norms to fuse in a wedding, where plentiful couples appear to have a lack of comprehension they need to work with and overcome the interracial differences, they will run across in their interracial wedding, especially for both races celebrate and respect their cultural traditions and heritage.